Cultural Gerontology: Towards an Understanding of Ethnicity and Aging - Holzberg, Carol S. (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1981)
While it is often taken for granted that the process of aging has its psychological, biological and sociological dimensions, gerontologists have not sufficiently explored the importance of cultural factors as these affect the aging process. The paper makes a plea for more studies in cultural gerontology by presenting a critical review of the non-anthropological literature on the "minority" and the ethnic elderly. Citing examples from her own fieldwork among elderly Jews in the Toronto Baycrest Centre, the author demonstrates the significance of ethnicity (a cultural variable) in easing the social and psychological problems that often accompany old age in urban North America.